Elastography as a new diagnostic tool to detect breast cancer – evaluation of research and clinical applications - Rzymski, Paweł; Opala, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
Mammography and ultrasonography are currently the most sensitive methods for detecting breast cancer, but elastography is a new diagnostic tool. Stiffness of invasive carcinomas were found to be 5-25 times larger than that of normal adipose tissue. There are basically two types of elastography examination used in initial clinical research: conventional elastography with compression and shear wave elastography. Analysis of 20 studies in the years 1997-2010 with 1484 malignant and 2822 benign breast lesions is presented in this paper. The overall sensitivity was 67-100% with specificity of 62-99% for elastography. This raises the hope of introducing this method in the BI-RADS classification and modifying diagnostics in category 3-4.